Effect of bio-degradable lubricating in the lubricant system of ICE engine - Hakim, Mohd Ikmal; Fikrie, Mohamad; Hanis, Nur Zulaika; Khalid, Amir; Zaman, Izzuddin (Penerbit UTHM, 2020)
The review paper focuses on the use of biodegradable lubricant as lubricant system. The best choice for formulating environmentally friendly lubricants are synthetic and biodegradable lubricant. The review has attempted to highlight a number of recent developments in the field of biodegradable synthetic ester base stocks for new generation lubricants, including efforts to date. In this study, efforts have been made within order to highlight some recent developments in the field of biodegradable synthetic ester base inventories for formulation of new generation lubricants. Developed products can be used either in single-or formulated formulations for automobile transport fluids, metal working fluids, cold rolling oils, fire-resistant hydraulic flows and industrial gear oils.